Late Aptian (Cretaceous) paleoceanography of the South Atlantic Ocean inferred from dinocyst communities of the Sergipe Basin, Brazil - Carvalho, Marcelo de Araujo; Bengtson, Peter; Lana, Cecilia Cunha (Paleoceanography, 2016)
The late Aptian (Early Cretaceous) is a crucial time interval for understanding the paleoceanographic changes in the Southern Hemisphere. Oceanographic changes in the emerging South Atlantic Ocean during this interval are reflected in the stratigraphic distribution of dinoflagellate communities recorded in the Muribeca and Riachuelo formations of the Sergipe Basin in northeastern Brazil. The Subtilisphaera community, in the lower and middle parts of the section, appears to be related to the Subtilisphaera Ecozone and suggests the onset of Tethyan influence in the central South Atlantic, in a restricted to inner-neritic environment. The succeeding Spiniferites community, in the middle part of the section, represents the first significant transgression, probably of eustatic origin. The Cyclonephelium-Exochosphaeridium community, in the upper part of the section, appears to be related to an oceanic event characterized by intermittent dysoxic-anoxic conditions. The uppermost part of the section is dominated by the Spiniferites community, related to a progressive regional transgression and culminating in an open-marine, fully Tethyan environment in the central part of the widening South Atlantic.
Gesehen am 29.04.2020